Rhinovirus species and clinical features in children hospitalised with pneumonia from Mozambique - Annamalay, A.; Lanaspa, M.; Khoo, S.; Madrid, L.; Acácio, S.; Zhang, Guicheng; Laing, I.; Gern, J.; Goldblatt, J.; Bizzintino, J.; Lehmann, D.; Le Souëf, P.; et al. (Blackwell Publishing Ltd, 2016)
© 2016 John Wiley & Sons Ltd. Objectives: To describe the prevalence of human rhinovirus (RV) species in children hospitalised with pneumonia in Manhiça, Mozambique, and the associations between RV species and demographic, clinical and laboratory features. Methods: Nasopharyngeal aspirates were collected from children 0 to 10 years of age (n = 277) presenting to Manhiça District Hospital with clinical pneumonia. Blood samples were collected for HIV and malaria testing, blood culture and full blood counts, and a chest X-ray was performed. A panel of common respiratory viruses was investigated using two independent multiplex RT-PCR assays with primers specific for each virus and viral type. RV species and genotypes were identified by seminested PCR assays, sequencing and phylogenetic tree analyses. Results: At least one respiratory virus was identified in 206 (74.4%) children hospitalised with clinical pneumonia. RV was the most common virus identified in both HIV-infected (17 of 38, 44.7%) and HIV-uninfected (74 of 237, 31.2%; P = 0.100) children. RV-A was the most common RV species identified (47 of 275, 17.0%), followed by RV-C (35/275, 12.6%) and RV-B (8/275, 2.9%). Clinical presentation of the different RV species was similar and overlapping, with no particular species being associated with specific clinical features. Conclusions: RV-A and RV-C were the most common respiratory viruses identified in children hospitalised with clinical pneumonia in Manhiça. Clinical presentation of RV-A and RV-C was similar and overlapping.